ChemInform Abstract: Direct Catalytic Enantio‐ and Diastereoselective Ketone Aldol Reactions of Isocyanoacetates. Issue 34 (August 2015) - de la Campa, Raquel; Ortin, Irene; Dixon, Darren J.
Abstract A diastereo‐ and enantioselective aldol/cyclization reaction of isocyanate esters with unactivated ketones to yield functionalized oxazolines is developed.